Radical innovation detection in the solar energy domain based on patent analysis - Feng, Sida; Han, Fang (Frontiers in Energy Research, 2023)
Introduction: Detecting radical innovations in the solar energy domain could offer innovation references and support the promotion of solar energy. However, relevant studies in the solar energy domain are lacking, and the related methods need to be improved. Methods: In this paper, a new framework to identify radical innovations in the solar energy domain is proposed by combining a technological convergence study and scientific relation analysis, and the link prediction method is utilized to detect potential radical innovations in this domain. Results: 1) The distributions of both the technological classes and scientific categories are uneven in the solar energy domain. The top 15 technological classes account for nearly 75.46% of all classifications. Fifteen scientific categories are cited by all the patents, and applied physics, multidisciplinary material science, energy and fuels play important roles in this domain. 2) The relationships among technological classes have evolved over time and have mainly focused on neighbouring disciplines. 3) A total of 130 patents containing new convergence relationships and/or closely related to science are identified as radical innovations. Radical innovative topics are related to the subdomains of solar photovoltaic (solar PV), heat storage, heat exchangers, and solar collectors. 4) Five potential radical innovative topics are identified. Automatic plants for producing electric energy, solar energy ecology houses, and so on are considered to have great potential in the future. Discussion: The results are consistent with the authoritative report and previous studies, which verify the viability of our methods. And the findings have important implications for scientists, policy-makers, and investors in this domain.